pls solve this question as soon as possible it would be of great help to me ....

Asked by  | 24th May, 2009, 12:08: PM

Expert Answer:

x4  + y4 -8x2 y2 = x4  + y4 -2x2 y2 - 6x2 y2

                          = (x2 +y2)  - 6x2 y2            .................eqn (1)

Now,

 x = 3+32    ⇒ x2 = 3 + 18 + 6 6 = 21 + 6 6

y =3 - 32    ⇒ y2 = 3 + 18 - 6 6 = 21 - 6 6

On sunbstitution in eqn (1)

x4  + y4 -8x2 y= (x2  - y2)  - 6x2 y2           

                         = (21 + 6 6 - 21 + 6 6) - 6(21 + 6 6)(21 - 6 6)

                         = 126 - 6 ((21)- (6 6)2)

Compute this to get the final answer.

 

Answered by  | 26th May, 2009, 04:19: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.